2022
DOI: 10.1002/adsc.202200980
|View full text |Cite
|
Sign up to set email alerts
|

Direct Assembly of Polysubstituted Furans with Dimethyl Sulfoxide as a Multipurpose Precursor via β‐C(sp3)−H Functionalization of Saturated Ketones

Abstract: An I2/K2S2O8 mediated multiple β‐C(sp3)−H functionalization reaction for the construction of polysubstituted furans has been established from readily available ethyl ketones and dimethyl sulfoxide. This transformation features dimethyl sulfoxide as a multipurpose precursor, acting as the precursor of the oxygen, methyl, and sulfur methyl units. Six new chemical bonds, involving two C−C, two C−O, and one C−S bonds were formed sequentially during the intermolecular oxidative annulation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Similarly, in 2022, Yang and Liu's group successfully realized the efficient utilization of DMSO as oxygen, methyl, and methylthio units by replacing aryl methyl ketones with ethyl ketones under the same conditions (Scheme 57C). 69…”
Section: Application Of the I2–dmso Reagent System To Aryl Methyl Ket...mentioning
confidence: 99%
“…Similarly, in 2022, Yang and Liu's group successfully realized the efficient utilization of DMSO as oxygen, methyl, and methylthio units by replacing aryl methyl ketones with ethyl ketones under the same conditions (Scheme 57C). 69…”
Section: Application Of the I2–dmso Reagent System To Aryl Methyl Ket...mentioning
confidence: 99%
“…A direct synthesis of polysubstituted furans through multiple C(sp 3 )-H functionalizations with more readily available materials is still required, hence Yang et al in 2022 reported an I 2 /K 2 S 2 O 8 mediated multiple β-C-(sp 3 )À H functionalization for the synthesis of 2,4,5-trisubstituted furans 219 from ethyl ketones 211 and dimethyl sulfoxide 212 in good to excellent yields. [115] Three types of cleavage of DMSO are involved in a one-step procedure to give polysubstituted furans. and EWGs in benzene ring such as Me, t Bu, OMe, CF 3 , and NO 2 groups were well tolerated (Scheme 29).…”
Section: Acid Catalyzed Approachesmentioning
confidence: 99%
“…Light yellow liquid (44.2 mg, 69% yield); R f = 0.21 (petroleum ether/EtOAc 5/1); 1 H NMR (600 MHz, CDCl 3 ): δ 8.09 (d,J = 2.4 Hz,1H),7.74 (dd,J = 2.4,8.4 Hz,1H),2H), 7.06 (t, J = 4.8 Hz, 1H), 7.01 (d,J = 8.4 Hz,1H), 4.61 (d, J = 12.0 Hz, 1H), 4.42 (d, J = 12.0 Hz, 1H), 3.95 (d,J = 11.4 Hz,1H),3.78 (d,J = 11.4 Hz,1H),2.91 (d,J = 13.8 Hz,1H), 2.88 (d, J = 13.8 Hz, 1H), 2.60 (br, 1H), 2.19 (s, 3H); 13 C{H} NMR (150 MHz, CDCl 3 ): δ 196.0, 160. 6,142.8,134.2,128.8,128.2,125.0,124.4,123.3,120.0,118.7,70.7,62.8,51.2,35.1,18.2;HRMS (ESI): m/z [M + H + ] calcd for C 16 H 17 O 3 S 2 , 321.0619; found, 321.0622.…”
Section: -(Hydroxymethyl)-3-((methylthio)methyl)-6-(thiophen-2-yl)chr...mentioning
confidence: 99%
“…5 Based on this, we envisaged that DMSO could provide a triple synthon that allows construction of structurally more complicated molecules containing a sulfur atom and a quaternary carbon center. 6 Sulfur-containing molecules are rather important, and their synthesis has attracted considerable interest due to their wide-ranging applications in pharmaceuticals, natural products, agrochemicals, and organic materials. 7 On the other hand, molecules with a quaternary carbon center are also very important and are found in many natural products and medicinal molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation